Magnetic Carbon Nanotubes for Protein Separation. (30th May 2012) - Diao, Xiuhui; Chen, Hongyu; Zhang, Guoliang; Zhang, Fengbao; Fan, Xiaobin
Abstract : Magnetic separation is a promising strategy in protein separation. Owing to their unique one-dimensional structures and desired magnetic properties, stacked-cup carbon nanotubes (CSCNTs) with magnetic nanoparticles trapped in their tips can serve as train-like systems for protein separation. In this study, we functionalized the magnetic CSCNTs with high density of carboxyl groups by radical addition and then anchored 3-aminophenylboronic acid (APBA) through amidation reaction to achieve oriented conjunction of antibodies (IgG). It was also demonstrated that the obtained magnetic CSCNTs-APBA-IgG conjugates could readily react with target antigens through specific antigen-antibody reaction and be used as new magnetic systems for protein separation.